(untitled) (International conference on multidisciplinary science, 2025)
Chronic hepatitis B (CHB) remains a significant global health burden, affecting approximately 296 million people worldwide. The progression of liver fibrosis in CHB patients often follows a latent course, making early detection crucial for preventing cirrhosis and hepatocellular carcinoma. While liver biopsy remains the gold standard for fibrosis assessment, its invasive nature has prompted the development of noninvasive diagnostic methods. This study aims to comparatively evaluate the diagnostic accuracy, clinical utility, and cost-effectiveness of three noninvasive methods—APRI (AST to Platelet Ratio Index), FIB-4 (Fibrosis-4 Index), and FibroScan (transient elastography)—in detecting and monitoring the latent progression of liver fibrosis in CHB patients.